Decreasing Influence of Summer Snow Cover Over the Western Tibetan Plateau on East Asian Precipitation Under Global Warming - Wang, Zhibiao; Wu, Renguang; Chen, Zhang; Zhu, Lihua; Yang, Kai; Liu, Kui; Yang, Yiya (Frontiers in Earth Science, 2021)
In recent years, some studies emphasized the influence of western Tibetan Plateau summer snow on the East Asian summer precipitation. With the temperature rise in the past decades, the snow cover over the western Tibetan Plateau in summer has significantly decreased. This raises the question whether the impact of the Tibetan Plateau snow has changed. The present study identifies a prominent change in the influence of the western Tibetan Plateau snow cover on the East Asian summer precipitation. Before the early 2000s, positive precipitation anomalies extend from the southeastern Tibetan Plateau through the Yangtze River to Japan and Korea and negative anomalies cover southeast China corresponding to more Tibetan Plateau snow cover. After the early 2000s, with the reduction of snow cover variability, below-normal and above-normal summer precipitation occurs over northern China-Mongolia and northeast Asia, respectively, corresponding to more Tibetan Plateau snow cover. The change in the influence of the Tibetan Plateau snow on the East Asian summer precipitation is associated with an obvious change in the atmospheric circulation anomaly pattern. Before the early 2000s, the wind anomalies display a south-north contrast pattern with anomalous convergence along the Yangtze River. After the early 2000s, an anomalous cyclone occupies Northeast China with anomalous southerlies and northerlies over northeast Asia and northern China, respectively. The Tibetan Plateau snow cover variation after the early 2000s is associated with the northeast Indian summer precipitation. The model experiments confirm that the weakened influence of summer western Tibetan Plateau snow cover on the East Asian atmospheric circulation and precipitation with the reduced snow cover anomalies.